Molecular epidemiology of HBV infection in chronic hepatitis B virus infected patients in northeast India. Issue 9 (28th April 2015) - Saikia, Anjan; Bose, Moumita; Barman, Narendra Nath; Deka, Manab; Thangkhiew, Rangsan Singh; Bose, Sujoy
<x xml:space="preserve">Abstract</x> The present study aimed to evaluate the molecular epidemiology of HBV in chronic HBV infected cases from northeast India (NEI), since scanty data are available from the region which has a predominant ethnically distinct tribal population. A total of 523 clinically diagnosed index chronic HBV infected cases and 172 asymptomatic patients (based on family screening) were enrolled with informed consent. Patients were stratified based on serology, imaging, pathology, and clinical data and grouped as chronic HBV and cirrhotic cohorts. Analysis for serum HBV DNA levels and HBV genotyping was performed, and was statistically co‐related with disease severity. Males were more prone to chronic HBV infection. Majority of the patients who had Chronic HBV infection based on family screening were females (59.88%), majorly wives of index patients. Mean viral load in Chronic HBV patients was almost 4.5‐folds higher than cirrhosis patients, and was significantly associated with e‐antigen positive status(P < 0.001) in both groups. HBV genotype D was the most prevalent genotype (62.30%) in NEI. Mixed genotype infection of A + D was found from Assam, along with C + D cases (1.29%) cumulatively. There is a high prevalence of HBV genotype C (13.96%) in our studied cohort which was found to be associated with higher viral load(P = 0.018), e‐antigen positivity(P = 0.043), and increased cirrhosis risk compared to Chronic HBV cases [OR = 1.670]. Family contacts in NEI are prone to infection with HBV and development of Chronic HBV. Higher presence of e‐positive cases and genotype C along with the mixed genotypes in NEI is unique and of significance with reference to predisposition to disease severity and even response to antiviral therapy. J. Med. Virol. 87:1539–1548, 2015. © 2015 Wiley Periodicals, Inc.